2012
DOI: 10.1007/s00198-012-1920-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal variation of hypovitaminosis D and its relationship to bone metabolism in healthy Hungarian men over 50 years of age: the HunMen Study

Abstract: A high prevalence of hypovitaminosis D and low BMD were observed in the studied Hungarian male population. This is the first study reporting higher 10-year hip and major osteoporotic fracture probability using the country-specific FRAX algorithm in individuals with hypovitaminosis D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 36 publications
4
30
2
3
Order By: Relevance
“…In our study, positive relationships were obtained between 25(OH)D status and BMD at all sites and such relationships persisted after adjustment for age, BMI, serum creatinine and calcium supplementation. Using the FRAX index, we demonstrated that low serum 25(OH)D levels were associated with a high 10-year probability of a hip fracture and a major osteoporotic fracture, which was a finding that was consistent with a previous report in healthy Hungarian men [37]. Supplementation with 800 IU vitamin D 3 and 1,200 mg calcium daily for 3 years reduced the risk of hip fracture by 43% and that of non-vertebral fracture by 32% [38].…”
Section: Discussionsupporting
confidence: 80%
“…In our study, positive relationships were obtained between 25(OH)D status and BMD at all sites and such relationships persisted after adjustment for age, BMI, serum creatinine and calcium supplementation. Using the FRAX index, we demonstrated that low serum 25(OH)D levels were associated with a high 10-year probability of a hip fracture and a major osteoporotic fracture, which was a finding that was consistent with a previous report in healthy Hungarian men [37]. Supplementation with 800 IU vitamin D 3 and 1,200 mg calcium daily for 3 years reduced the risk of hip fracture by 43% and that of non-vertebral fracture by 32% [38].…”
Section: Discussionsupporting
confidence: 80%
“…[2][3][4][5][6][7] Vitamin D exists in two forms: vitamin D2 or ergocalciferol which is found naturally in foods of plant origin, and vitamin D3 or cholecalciferol which is mainly synthesized in the skin by exposure to ultraviolet-B light and is also abundant in foods of animal origin. The main source of vitamin D is via exposure of the human skin to sunlight between 10am and 3pm in the spring, summer and fall.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattoa és mtsai 50 év feletti egészséges férfiak D-vitamin-státu-szát vizsgálták és vetették össze a FRAX ® -értékekkel [20]. Egy másik vizsgálatban diabeteses betegek körében mérték fel a törési rizikót [21].…”
Section: áBra)unclassified